STUDY ON THE EFFECTIVENESS OF ADDING SOME PLANT EXTRACTS WITH BHT ON MEAT QUALITY OF LAMB PATTIES DURING CHILLING STORAGE - Ibrahim, A. Baker (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This experiment was aimed to evaluate and compare the effects of adding natural extracts (clove, Mentha and thyme) with synthetic BHT on some physiochemical, microbial, and sensory characteristics of lamb patties stored at 4 Cº for 12 days. Results indicated that there’s a steady rise (P<0.01) in oxidative rancidity, microbial and pH with the increasing time of storage. Also, a significant (P<0.01) reduction in TBA, microbial and pH was observed in patties treated with clove, thyme, mentha and BHT as compared with untreated samples. It was found that adding natural extracts is more effective in inhibiting microbial count than did BHT. The highest score of overall acceptability was noticed in patties blended with thyme and mentha, and the lowest was recorded in control samples